The Effectiveness of Oxytocin Massage and Lavender Aroma Therapy on The Optimization of Breastfeeding Breast-Feeding Women in North Tapanuli District - Riance Mardiana Ujung; Naomi Isabella Hutabarat (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
The puerperium is the process of giving birth to a mother starting from the birth of a baby, the birth of the placenta and until the recovery or return of the reproductive organs to their original form before pregnancy which lasts 42 days. The puerperium is the process of giving birth to a baby until the recovery that the mother goes through which is used to restore her health or after childbirth the removal of the plaque and ends when the cervix organs regain their pre-gestational condition. The aim of this research is to analyze the determinants of whether and how effective oxytocin massage is for postpartum mothers. The participants of this study were all parturient women who were pregnant in North Tapanuli district. Meanwhile, the research sample comprises 30 parturients, consisting of 15 people in the intervention group with oxytocin massage and 15 people in the control group who were given lavender aroma therapy. The sampling technique uses accidental sampling. The data analysis method for this research is univariate data analysis aimed at obtaining the frequency distribution of each variable studied and presented. This research aims to see the influence of the independent variable on the dependent variable. The analysis of this research used the Independent Sample T-Test which aims to see the differences in oxytocin massage with lavender aroma therapy between the study group that has an effect and the group that can be controlled. Criteria for decision making results using the Mann Whitney approach.The mandatory output of the research is to be published on Sinta 3 and the additional output is to produce an Oxytocin Massage Video. The results of research using the Mann Whitnney approach obtained a measurement result of p value = 0.828 (α > 0.05), meaning that there is no comparison on the treatment effectiveness of occitocin massage and lavender aroma therapy in optimizing breast milk output of breast milk production in parturient mothers in the Siborong-borong Community Health Center, Pangaribuan, Sipahutar and Siatas Barita in 2024. Keyword: Aromatherapy, Breast Milk, Oxytocin Massage, Postpartum Mother